(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Individuals with paralysis or severe physical disabilities often face significant barriers in communicating their needs, which can limit their independence and quality of care. This study presents a novel system that translates hand movements into corresponding audio messages and displays them on an LCD, enabling effective communication between patients and caregivers. The device incorporates a 3-axis accelerometer and a microcontroller that processes directional hand gestures to generate preprogrammed messages. Testing demonstrates that the system reliably interprets four primary gestures corresponding to the messages: “I am hungry,” “I want to go to the bathroom,” “I want to watch television,” and “I want to go out.” The device operates effectively for users with partial mobility and accommodates those with speech impairments. Maximum speaker volume is 60 dB, with an operational range of approximately 2 meters. The system provides a practical and low-cost assistive technology solution that may improve patient autonomy, caregiver responsiveness, and quality of life.